Introducing the New Definition and Diagnostic Criteria of Disseminated Intravascular Coagulation Released by the International Society on Thrombosis and Haemostasis in 2025 - Iba, Toshiaki; Maier, Cheryl L.; Scarlatescu, Ecaterina; Levy, Jerrold H. (Seminars in Thrombosis and Hemostasis, 2025)
In 2025, the International Society on Thrombosis and Haemostasis (ISTH) released updated definitions and diagnostic criteria for disseminated intravascular coagulation (DIC), reflecting advances in understanding its pathophysiology. DIC is now defined as an acquired, life-threatening condition involving systemic coagulation activation, impaired fibrinolysis, and endothelial injury. The revised framework emphasizes the condition's dynamic nature, progressing from preclinical abnormalities to overt clinical manifestations such as bleeding and organ dysfunction. A major innovation in the 2025 update is the phase-based classification of DIC: Pre-DIC, early-phase DIC, and overt DIC. Early-phase DIC—also referred to as subclinical or compensated DIC—is characterized by laboratory abnormalities preceding clinical symptoms. Overt DIC represents the advanced stage with clear evidence of coagulopathy and organ failure. Importantly, the new criteria are tailored to the underlying disease, such as sepsis, trauma, or malignancy. For example, the sepsis-induced coagulopathy score is now acknowledged as a tool for detecting early-phase DIC in septic patients. The overt DIC scoring system has been refined, including revised D-dimer thresholds: Levels >3× and >7 × , the upper normal limit now corresponds to 2 and 3 points, respectively. Platelet count, prothrombin time-international normalized ratio, and fibrinogen levels remain key indicators. The criteria also classify DIC into thrombotic and hemorrhagic phenotypes. Thrombotic DIC is marked by microvascular thrombosis and organ dysfunction, while hemorrhagic DIC is characterized by bleeding due to consumption of coagulation factors. By introducing clearer definitions and individualized approaches, these updates aim to enable earlier diagnosis and more effective management of DIC across clinical contexts.
Keywords: disseminated intravascular coagulation; definition; diagnostic criteria; sepsis; anticoagulation